The American Heart Association 2030 Impact Goal: A Presidential Advisory From the American Heart Association. Issue 9 (3rd March 2020) - Angell, Sonia Y.; McConnell, Michael V.; Anderson, Cheryl A.M.; Bibbins-Domingo, Kirsten; Boyle, Douglas S.; Capewell, Simon; Ezzati, Majid; de Ferranti, Sarah; Gaskin, Darrell J.; Goetzel, Ron Z.; Huffman, Mark D.; Jones, Marsha; et al.
Abstract : Each decade, the American Heart Association (AHA) develops an Impact Goal to guide its overall strategic direction and investments in its research, quality improvement, advocacy, and public health programs. Guided by the AHA's new Mission Statement, to be a relentless force for a world of longer, healthier lives, the 2030 Impact Goal is anchored in an understanding that to achieve cardiovascular health for all, the AHA must include a broader vision of health and well-being and emphasize health equity. In the next decade, by 2030, the AHA will strive to equitably increase healthy life expectancy beyond current projections, with global and local collaborators, from 66 years of age to at least 68 years of age across the United States and from 64 years of age to at least 67 years of age worldwide. The AHA commits to developing additional targets for equity and well-being to accompany this overarching Impact Goal. To attain the 2030 Impact Goal, we recommend a thoughtful evaluation of interventions available to the public, patients, providers, healthcare delivery systems, communities, policy makers, and legislators. This presidential advisory summarizes the task force's main considerations in determining the 2030 Impact Goal and the metrics to monitor progress. It describes the aspiration that these goals will be achieved by working with a diverse community of volunteers, patients, scientists, healthcare professionals, and partner organizations needed to ensure success.